The Effect of Human Doll Media Usage on the Special Program of Reproduction Health towards the Ability of Self-Care of Reproduction Health for Students with Hearing Impairment at SMPLB Malang - Rina Wati; Sihkabuden Sihkabuden (Department of Special Education, 2017)
Students with hearing impairment can not hear well as result they find difficultis in learning a abstract material. This study tried to describe the effect of the use of human doll media on reproductive health towards the ability of reproductive health care for the students with hearing impairment. The method was a quasi experimental research with One-group pretest and posttes design. The analysis technique used was the nonparametric Wilcoxon test. The results of the study was the human doll media on a special program of reproductive health have effect on the ability of reproductive health care for students with hearing impairment. The recommendations addressed for teachers is to implement the use of human doll media about reproductive health in the learning process.Siswa tunarungu adalah anak yang tidak mampu mendengar mengakibatkan sulit memahami materi pembelajaran yang bersifat abstrak. Penelitian ini bertujuan untuk menganalisis pengaruh penggunaan media boneka human doll pada program khusus kesehatan reproduksi terhadap kemampuan merawat kesehatan reproduksi. Metode penelitian yang digunakan adalah quasi experiment dengan desain penelitian One-group pretest and posttes design. Teknik analisis menggunakan uji Wilcoxon. Hasil penelitian penggunaan media boneka human doll berpengaruh pada program khusus kesehatan reproduksi terhadap kemampuan merawat kesehatan reproduksi siswi tunarungu di SMPLB B YPTB Malang. Saran ditujukan kepada guru untuk menerapkan penggunaan media boneka human doll pada pembelajaran program khusus kesehatan reproduksi.